PEMBERIAN EKSTRAK DAUN SIRSAK (Annona muricuta) UNTUK MEMPERBAIKI KERUSAKAN SEL BETA PANKREAS MELALUI PENURUNAN KADAR GLUKOSA DARAH, ADVANCED GLYCATION AND PRODUCT DAN 8-HIDROKSI-2-DIOKSIGUANOSIN PADA TIKUS WISTAR HIPERGLIKEMIA - Adhi Suastuti, Ni G. A. M. Dwi; Panca Dewi, I G. A. Kunti Sri; Ariati, Ni Komang (Jurnal Kimia (Journal of Chemistry), 2015)
This research aimed to determine the effectivity of soursop leaf extract to repair beta pancreatic cells damaged in Wistar rats induced by alloxan. This experiment used randomized posttest-only control group design . In this experiment, 24 Wistar rats were used which divided into four groups, control group (K), and three treatment groups (P). P1 was the group tretment with a dose of 50 mg/kg bw/day, P2 with a dose of 100 mg/kg bw/day,  and P3 was the group treatment with a dose of 150 mg/kg bw/day extract. All groups were induced by alloxan with a dose of 150 mg/kg bw to obtain condition of hyperglycemia. The results showed that blood glucose levels decreased after treatment with the extracts. Glucose levels in group K, P1, P2, and P3 were 208.0 mg/dL; 177.5mg/dL; 164.7 mg/L and 137.0 mg/dL respectively. After 2 weeks of treatment, the level of 8-OHdG and AGEs were also reduced. The lowest level was observed in P3 treatment which the level of 8-OHdG 1.664ng.mL and 0.033 mol/L for AGEs level. In conclusion the soursop leaf ( Annona muricata) extract given at a dose of 150 mg/kg bw/day can improve beta pancreatic cells resulted from antioxidant activity content in the extract which function as antihyperglycemia. Based on GC-MS spectra analysis,  the the soursop leaf ( Annona muricata) extract consisted of caryophyllene, ethyl tetradekanoat, acid 2-cyclohexane-1-one, 4-hydroxy-3,5,6-trimethyl-4-(3-oxo-1-butenyl), hexa ethyl decanoate , phytol, thiazole-2,4 (3H, 5H) _dion, 5 benzilideno-3 [etifenilamino) metal], 9-octadecanoic acid, ethyl linoteat, ethyl oleate and ethyl octadecanoic.
Keywords: Soursop leaf, blood glucose levels, hyperglycemia, AGEs, 8-OHdG